Impact of Silicone Arch Support on Energy Expenditure in Flexible Flatfeet Employees - Erwinsyah, Belva Lativa Putri; Putra, Raden Achmad Candra; Karma, Agusni (Poltekkes Kemenkes Jakarta I, 2024)
Background: Flat feet, or pes planus, is a common condition affecting approximately 20-30% of the general population, leading to muscle tension and instability that can impact energy expenditure during walking. Objective: To evaluate the effectiveness of Silicone Medial Arch Support in reducing energy expenditure during walking in individuals with flat feet compared to a control group. Methods: A total of 32 participants with flexible flat feet were selected through random sampling. This study employed a quasi-experimental design with a control group using a sham insole and an intervention group using silicone medial arch support for two months. Energy expenditure was measured using VO? max. The average energy expenditure before using silicone medial arch support was 36.76 ± 5.03 ml/kg/min, which increased to 39.75 ± 4.05 ml/kg/min post-intervention (p < 0.001). For the sham insole group, the energy expenditure was 34.67 ± 2.44 ml/kg/min before and 34.87 ± 2.20 ml/kg/min after the intervention (p = 0.183). Results: The use of silicone medial arch support resulted in a significant increase in energy expenditure compared to the sham insole group (p < 0.001). Conclusion: The study concludes that silicone medial arch support can reduce energy expenditure during walking in individuals with flat feet. These results suggest that incorporating well-designed arch support interventions can significantly improve biomechanical efficiency and comfort for individuals with flat feet. Future interventions should consider individual variations in foot morphology and activity levels to optimize support design, potentially integrating adjustable or customizable insoles to better address the diverse needs of this population.